COMPARATIVE STUDY ON THE ANTIOXIDANT ACTIVITIES OF METHANOLIC AND AQUEOUS EXTRACTS OF TERMINALIA BELLERICA - GUPTA, RASNA; SINGH, RAM LAKHAN; GUPTA, ANKIT (International Journal of Current Pharmaceutical Research, 2019)
Objective: The present study was undertaken to investigate the antioxidative activity of fruit pulp, seed and bark of T. bellerica. Methods: Methanol (70%) and water were used for the extraction, and the respective extracts were analyzed for total phenolic contents along with the antioxidant activities through different assays. Results: Amongst the tested extracts, methanolic extracts were found to be better than aqueous with the highest total phenolic contents (TPC). Methanolic fruit pulp showed lower IC50 for free radical (118.7 µg/ml), superoxide anion radical (77.65 µg/ml) and hydroxyl radical (73.76 µg/ml) scavenging activities. Methanolic fruit pulp also showed lower IC50 for lipid peroxidation (115.6 µg/ml) and ferric thiocyanate (184.98 µg/ml) assay than aqueous extracts in comparison to standard quercetin. Further, correlation between TPC and antioxidant studies revealed that phenolics are mainly responsible for antioxidant activity of T. bellerica. Conclusion: The current study suggests that the methanolic extract of T. bellerica could be a potential source of natural antioxidants for food and pharmaceutical companies.